Tempol (4 hydroxy-tempo) inhibits anoxia-induced progression of mitochondrial dysfunction and associated neurobehavioral impairment in neonatal rats - Samaiya P.K.; Narayan G.; Kumar A.; Krishnamurthy S. (My University, 2025)
Background Anoxia leads to a robust generation of reactive oxygen species/nitrogen species which can result in mitochondrial dysfunction and associated cell death in the cerebral cortex of neonates. Aim The present study investigated the pharmacological role of tempol in the treatment of rat neonatal cortical mitochondrial dysfunction induced insult progression (day-1 to day-7) and associated neurobehavioral alterations post-anoxia. Methods Rat pups of 30 h age or postnatal day 2 (PND2) were randomly divided into 5 groups (n = 5 per group): (1) Control; (2) Anoxia; (3) Anoxia + Tempol 75 mg/kg; (4) Anoxia + Tempol 150 mg/kg; and (5) Anoxia + Tempol 300 mg/kg, and subjected to two episode of anoxia (10 min each) at 24 h of time interval in an enclosed chamber supplied with 100% N2. Results Tempol significantly decreased nitric oxide ([rad]NO) formation and simultaneously improved superoxide dismutase (SOD) and catalase (CAT) activities. Further, we observed a significantly (P < 0.05) improvement in mitochondrial respiration, complex enzyme activities, mitochondrial membrane potential (MMP) along with attenuation of transition pore opening (MPT) after treatment with tempol. Furthermore, tempol decreased expression of mitochondrial Bax, cytochrome-C, caspase-9 and caspase-3 while the increase in expression of cytoplasmic Bax, mitochondrial Bcl-2 on day-7 in cortical region indicating regulation of intrinsic pathway of apoptosis. Further, it improved anoxia-induced neurobehavioral outcome (hanging and reflex latencies). Conclusion Biochemical, molecular and behavioral studies suggest the role of tempol in preserving mitochondrial function and associated neurobehavioral outcomes after neonatal anoxia. © 2017 Elsevier B.V.